ANALYSIS OF MERCURY (HG) LEVEL IN GOLD PROCESSING CONTAINER USING TRADITIONALTOOL IN PAYA ATEUK VILLAGE, PASIE RAJA, SOUTH ACEH - Susy Sriwahyuni; Darmawan Darmawan; Maiza Duana (RADJA PUBLIKA, 2022)
Mining activities has some negative effects. One of them is mercury pollution caused by gold processing through amalgamation. The data of this study was collected through mercury parameters analysis on liquid waste in laboratory. The examination of sample was carried out at Laboratory of Research and Industrial Development and Industrial Standardization Institute in Banda Aceh. The sample used was traditional gold processing water in Paya Ateuk Village, SouthAceh. The results showed the value of mercury level is 0.0149 mg/l or above the specified threshold. Improving the management of traditional gold processing is not only the responsibilityof miners, but also involve cross sectoral so that mercury does not pollute the environment.